Topology optimization of magnetic cores for WPT using the geometry projection method. Issue 3 (25th October 2021) - Otomo, Yoshitsugu; Igarashi, Hajime
Abstract : Purpose: The purpose of this study is to search for an optimal core shape that is robust against misalignment between the transmitting and receiving coils of the wireless power transfer (WPT) device. During the optimization process, the authors maximize the coupling coefficients while minimizing the leakage flux around the coils to ensure the safety of the WPT device. Design/methodology/approach: In this study, a novel topology optimization method for WPT devices using the geometry projection method is proposed to optimize the magnetic core shape. This method facilitates the generation of bar-shaped magnetic cores because the material distribution is represented by a set of elementary bars. Findings: It is shown that an optimized core shape, which is obtained through topology optimization, effectively increases the net magnetic flux interlinked with the receiving coil and outperforms the conventional core. Originality/value: In the previous topology optimization method, the material distribution is represented by a linear combination of Gaussian functions. However, this method does not usually result in bar-shaped cores, which are widely used in WPT. In this study, the authors propose a novel topology optimization method for WPT devices using geometry projection that is used in structural optimization, such as beam and cantilever shapes.